2012
DOI: 10.1111/jfs.12003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zataria multiflora Boiss. Essential Oil on Growth and Citrinin Production by Penicillium citrinum in Culture Media and Mozzarella Cheese

Abstract: In the present work, the effects of Zataria multiflora Boiss. essential oil (EO) against growth and citrinin production by Penicillium citrinum ATCC 1156 were evaluated in culture media and mozzarella cheese. The growth was completely inhibited at 200 ppm on potato dextrose agar, and minimum fungicidal concentration of the EO was estimated at 400 ppm. EO strongly suppressed the growth and citrinin formation in media with a dose‐dependent manner. At 200 ppm in yeast extract sucrose (broth) flasks, mycelial dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
1
9
1
Order By: Relevance
“…; Noori et al . ; Sajed et al . ) and could lead to the reduction of micro‐organisms, some of which are positive decarboxylase and responsible for producing BAs.…”
Section: Resultsmentioning
confidence: 99%
“…; Noori et al . ; Sajed et al . ) and could lead to the reduction of micro‐organisms, some of which are positive decarboxylase and responsible for producing BAs.…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies reported the antifungal effects of the liquid phase of EOs in cheese (Gandomi et al, 2009;Jeong et al, 2014;Noori et al, 2012). The antifungal effect of Z. multiflora EO in the liquid phase against A. flavus in culture media and Iranian white cheese has been investigated (Gandomi et al, 2009).…”
Section: Storage Daymentioning
confidence: 99%
“…is an aromatic plant endemic to Iran, Pakistan, and Afghanistan; and locally known as “Avishane Shirazi” (Aliakbarlu et al, 2013 ; Shaiq Ali et al, 2000 ). Z. multiflora essential oil (ZEO) has various biological activities, including antioxidant, antibacterial, and antifungal activities (Aliakbarlu et al, 2013 ; Gandomi et al, 2009 ; Noori et al, 2012 ). Meanwhile, the antifungal activity of the liquid phase of ZEO against Aspergillus flavus in culture media and cheese model has also been reported (Moosavi‐Nasab et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…; Noori et al . ). The components of clove and thyme, i.e., eugenol and thymol, respectively, have been reported to inhibit P. citrinum growth and citrinin production as reported by Vazquez et al .…”
Section: Introductionmentioning
confidence: 97%